Pharmacokinetics and Excretion of Berberine and Its Nine Metabolites in Rats - Feng, Xinchi; Wang, Kun; Cao, Shijie; Ding, Liqin; Qiu, Feng (Frontiers in Pharmacology, 2021)
Berberine, a well-known alkaloid, has been proved to possess various pharmacological activities. Previous studies demonstrated that berberine could be extensively metabolized and the metabolites also contributed to its therapeutic effects. However, as for berberine’s metabolites, especially phase II metabolites, pharmacokinetics and excretion studies were rarely reported. The objective of this study was to thoroughly investigate the pharmacokinetic and excretion profiles of berberine and its nine metabolites, namely, berberrubine (M1), demethyleneberberine (M2), jatrorrhizine (M3), jatrorrhizine-3-O-β-D-glucuronide (M4), jatrorrhizine-3-O-sulfate (M5), thalfendine-10-O-β-D-glucuronide (M6), berberrubine-9-O-β-D-glucuronide (M7), demethyleneberberine-2-O-sulfate (M8) and demethyleneberberine-2-O-β-D-glucuronide (M9) in rats. An accurate and reliable LC-MS/MS method was developed and validated for the determination of berberine and its nine metabolites in rat biosamples. Pharmacokinetic profiles of berberine and its nine metabolites were obtained after a single intravenous administration (4.0 mg/kg) and oral administration (48.2, 120 or 240 mg/kg) of berberine in rats. For excretion study, rats were intragastrically administered a single dose of 48.2 mg/kg berberine. Our results showed that berberine could be metabolized rapidly and all the nine metabolites could be detected in vivo. The absolute bioavailability of berberine was 0.37 ± 0.11%. As for the AUC0-t values, phase II metabolites were much higher than those of phase I metabolites, suggesting that phase II metabolites were the major metabolites exist in blood circulation. 18.6% of the berberine was excreted in feces as berberrubine (M1). The total recovery of berberine and its nine metabolites from urine, bile and feces was 41.2%. This is the first systematic study about the pharmacokinetics and excretion of berberine and its nine metabolites, which will be beneficial for both better understanding the clinical effects and further development of berberine.